2011
DOI: 10.1080/02672571003719070
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of marketing academics, neurologists, and marketing professionals about neuromarketing

Abstract: Neuromarketing uses the latest advances in brain scanning to learn more about the mental processes behind customer purchasing decisions. The purpose of this exploratory research was to reveal the perceptions of marketing academics, neurologists, and marketing professionals regarding neuromarketing studies, as they have an important role for the future of neuromarketing studies. Quantitative analysis was conducted on data from 111 marketing academics, 52 neurologists, and 56 marketing professionals. All partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 25 publications
1
81
0
5
Order By: Relevance
“…Many authors still use the terms "study of brain imaging" (Hubert & Kenning, 2008;Perrachione & Perrachione, 2008;Babiloni, 2012;Reynolds, 2006;Garcia & Saad, 2008;Green & Holbert, 2012), "study of neuroimaging" (Eser et al, 2011 andVecchiato et al, 2012), and "neuro-technology" (Murphy et al, 2008 andFisher et al, 2010) to refer to neuromarketing (Perrachione & Perrachione, 2008;Green & Holbert, 2012;Javor et al, 2013;Orzán et al, 2012;Fugate, 2007 andMorin, 2011). This usage most likely occurs because fMRI is the most prominent technique under the academic and market spotlights, although the neuromarketing studies identified in this work go beyond brain imaging.…”
Section: Definition Of Neuromarketingmentioning
confidence: 99%
See 4 more Smart Citations
“…Many authors still use the terms "study of brain imaging" (Hubert & Kenning, 2008;Perrachione & Perrachione, 2008;Babiloni, 2012;Reynolds, 2006;Garcia & Saad, 2008;Green & Holbert, 2012), "study of neuroimaging" (Eser et al, 2011 andVecchiato et al, 2012), and "neuro-technology" (Murphy et al, 2008 andFisher et al, 2010) to refer to neuromarketing (Perrachione & Perrachione, 2008;Green & Holbert, 2012;Javor et al, 2013;Orzán et al, 2012;Fugate, 2007 andMorin, 2011). This usage most likely occurs because fMRI is the most prominent technique under the academic and market spotlights, although the neuromarketing studies identified in this work go beyond brain imaging.…”
Section: Definition Of Neuromarketingmentioning
confidence: 99%
“…Neuromarketing has also been identified as a way of shaping companies' marketing strategies (Eser et al, 2011). Publicity and advertising have been described as the areas of marketing that have benefited the most from neuromarketing techniques.…”
Section: Importance Of Neuromarketing To Marketing Studiesmentioning
confidence: 99%
See 3 more Smart Citations